2018
DOI: 10.3892/mmr.2018.9774
|View full text |Cite
|
Sign up to set email alerts
|

Identification of differentially expressed genes in MG63 osteosarcoma cells with drug‑resistance by microarray analysis

Abstract: Osteosarcoma is the most common type of primary malignant bone tumor, with extremely poor prognosis in patients with metastatic disease and resistance to therapy, such as multidrug regimens. The mechanisms of drug resistance are quite complex and have not been fully elucidated; thus, novel therapeutic targets should be identified to alleviate drug resistance in osteosarcoma. In the present study, the transcriptomes of the human osteosarcoma cell line MG63 and vincristine (VCR)-resistant MG63 cells were compare… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 25 publications
0
6
0
Order By: Relevance
“…Furthermore, molecular docking results showed that vincristine, dexamethasone, and vinblastine all bound well to the key targets RUNX2, OMD, and CD4. Vincristine, dexamethasone, and vinblastine are common drugs used to treat OS (Boscoboinik et al, 1994;Ahlström et al, 2005;Chen et al, 2019). These results suggested that these five key targets could be potential targets for OS treatment.…”
Section: Discussionmentioning
confidence: 90%
“…Furthermore, molecular docking results showed that vincristine, dexamethasone, and vinblastine all bound well to the key targets RUNX2, OMD, and CD4. Vincristine, dexamethasone, and vinblastine are common drugs used to treat OS (Boscoboinik et al, 1994;Ahlström et al, 2005;Chen et al, 2019). These results suggested that these five key targets could be potential targets for OS treatment.…”
Section: Discussionmentioning
confidence: 90%
“…With the development of new therapeutic technologies, the survival rate of patients with OS has markedly increased. However, the overall outcome of patients with OS remains poor due to drug or multidrug resistance (19,20). Thus, the study of the mechanisms responsible for the development of OS and the identification of novel effective treatable methods for patients with OS is crucial.…”
Section: Discussionmentioning
confidence: 99%
“…MG-63 and Saos-2 cells were provided by the China Center for Type Culture Collection as in our previous study ( Shu et al, 2020 ). MG-63 and Saos-2 cells were cultured in RPMI‑1640 and McCoy’s 5A medium (Gibco; Thermo Fisher Scientific, Inc., Waltham, MA, USA), respectively, supplemented with 10% FBS (Gibco; Thermo Fisher Scientific, Inc., Waltham, MA, USA), 1% L‑glutamine, and 1% penicillin‑streptomycin sulfate (Thermo Fisher Scientific, Inc., Waltham, MA, USA) at 37 °C in a 5% CO 2 humidity-controlled incubator ( Chen et al, 2019 ; Zhou et al, 2016 ).…”
Section: Methodsmentioning
confidence: 99%